P1-S1.49 Syphilis prevalence and risk factors in Brazilian Armed Forces conscripts, 2007. (10th July 2011) - Ribeiro, D; Pinto, V M; Rezende, E; Espinosa, A; Pereira, G
Abstract : The aim of this study was to describe the syphilis prevalence by geographic region and frequency of behaviours and symptoms related to STDs. A cross-sectional study was performed with Brazilian Armed Forces draftees in 2007. They answered a self-administered questionnaire on sociodemographic issues, sexual practice and condom use, STD symptoms and had a blood sample collected for syphilis test. A total of 35 460 draftees answered the questionnaire and 75.5% of these had already had sexual intercourse. Overall syphilis prevalence was 0.53% (95% CI 0.45% to 0.61%). By geographic region—North (0.85%), Northeast (0.82%), being almost double the Midwest region (0.49%) and more than double the Southeast (0.34%) and Southern region (0.26%). Being 17 years old [OR=1.3 (95% CI 1.05 to 1.73)], having completed primary education [OR=1.5 (95% CI 1.03 to 2.22)], living in the North/Northeast region of the country [OR=1.2 (95% CI 1.04 to 1.36)], reporting a history of STD [OR=2.7 (95% CI 1.03 to 6.99)], being MSM [OR=4.5 (95% CI 2.59 to 7.81)], and reporting genital ulcer disease [OR=2.6 (95% CI 1.59 to 4.26)] were associated with syphilis. Addressing the young at the time of military enlistment may be a good moment to consider new strategies for accessing and counselling this population, thus allowing the implementation of a more appropriate healthcare policy.